Avaliação da limpeza de CDtrodo construídos a partir de CD de ouro gravável/fita adesiva de galvanoplastia - Foguel, M. V. [UNESP]; Uliana, C. V. [UNESP]; Tomaz, P. R.U. [UNESP]; Marques, P. R. B. Oliveira [UNESP]; Yamanaka, H. [UNESP]; Ferreira, A. A. Pupim [UNESP] (Ecletica Quimica, 2009)
Gold electrodes are widely used in electrochemistry and electroanalytical chemistry, due to the high purity, broad range of work potential as well as the possibility to control and modify the surface. On this work construction and cleaning of electrodes from gold recordables compact discs (CD-Rs), namely CDtrodes, are described. The CDs was submitted to the action of concentrated HNO3 in order to remove the protection layer and to expose the metallic layer; the electrode area was delimited by using galvanoplasty tape. The literature has been published many articles on CDtrode focused on the application but not on the cleaning; there is no register on galvanoplasty tape to define electrode area. Several methods for gold surface cleaning after attack of HNO3 were investigated, such as application of fixed potential in NaCl solution, successive scans in H2SO4 and ultrasound application, and best results were obtained in H2SO4 solution. This electrode material is interesting due to the performance comparable to the commercial electrodes, besides great versatility and low cost.
Evaluation of the CDtrode cleaning constructed from gold recordable CD/galvanoplasty tape
Keywords: CDtrode, CD-R electrodes; Cyclic voltammetry; Gold surface cleaning